Kinerja Penyuluh Pertanian di Kabupaten Pidie Provinsi Aceh dalam Melaksanakan Tugas dan Fungsi - Mujiburrahmad Mujiburrahmad; Pudji Muljono; Dwi Sadono (Jurnal Penyuluhan, 2014)
Various programs and the results achieved must not be separated from the role of agricultural extension in carrying out their duties and responsibilities in fostering farmer. The purpose of the study to identify the level of performance of agricultural extension in Pidie District in carrying out their duties, and to analyze the factors associated with the performance of agricultural extension. The method used in data collection is the census. The number of respondents in this study were as many as 47 people. The data collection was carried out from February 2014 to April 2014, using questionnaires, interviews, observation and study of literature. The data obtained were tabulated and then analyzed using Spearman Rank. The results showed that the level of performance of agricultural extension in Pidie District in general is still relatively low. Spearman rank correlation results showed: (1) factors related to the internal characteristics of the performance of extension are: length of service and number of target groups (2) factors related to the external characteristics of the performance of extension are: administrative support and working conditions, and (3) Factors competence extension tasks related to the performance of agricultural extension are: the application of adult learning principles, communication skills and ability to cooperate.Keywords: agricultural extension, performance, characteristics, competencies.